Hydrometallurgical Recovery of Cobalt from Spent Lithium-Ion Battery (LiCoO2) using Organic Acids - Catur Rini Widyastuti; Artanti Estiningtyas; Indah Cahyani Puspitaningrum; Siti Ajeng Muslimah; Shafa Noviandrea Towidjojo; Danang Subarkah Hadikawuryan; Rizki Setiadi; Aryo Baskoro Utomo; Muhammad Olvianas (Rekayasa, 2025)
The increasing use of portable electronic devices has led to an increase in lithium-ion battery (LiB) waste, which contains hazardous metals such as cobalt. It is noteworthy that cobalt accounts for up to 30% of the battery weight, significantly higher than its concentration in natural ores (<1%). Conventional recovery methods use strong inorganic acids (e.g., H₂SO₄, HCl), which are effective but produce hazardous wastewater and require complex treatment procedures. In this study, the cobalt extraction process was carried out using a hydrometallurgical method using organic acids, specifically ascorbic acid and citric acid. The extraction process was carried out with variations in organic acid concentrations ranging from 0.5 M to 2.5 M at temperatures of 55°C and 70°C. The extracted liquid was collected and analyzed for cobalt content using an Atomic Absorption Spectrophotometer (AAS). The cobalt leaching process using citric acid successfully dissolved 13.58–13.89 mg/L of cobalt. Meanwhile, from the leaching process with ascorbic acid, dissolved cobalt was obtained in the range of 10.96–12.87 mg/L. Based on the data obtained from the leaching process using organic acids, it can be seen that the best leaching process was obtained with citric acid at a concentration of 0.5 M at a temperature of 55°C, which produced 13,837 mg/L of dissolved cobalt. The extracted cobalt can be used for the synthesis of cobalt acetate, which is a fine chemical. However, not all cobalt dissolved in the leaching process can be precipitated to produce cobalt acetate. Of all the leaching solutions with both organic acids at different concentrations, only the solution from the leaching process with ascorbic acid at a concentration of 0.5 M was successfully precipitated and further synthesized into cobalt acetate with a yield of 17.42 wt%. In addition, FTIR analysis confirmed that the synthesized cobalt acetate was consistent with the reference cobalt(II) acetate tetrahydrate, with the difference in intensity indicating lower hydration in the synthesized sample.